THE PERCEPTIONS OF ENTREPRENEURS ON THE STRATEGIC ROLE OF HUMAN RESOURCE MANAGEMENT - L., Dr. Phawick; Pro. Prabou T (International Journal of Multidisciplinary Research and Studies, 2021)
In literature, many sorts of research on human resource management and entrepreneurship are developed. However, there is only some sort of research on the perception of entrepreneurs on the strategic role of human resource management. This study investigates the role of human resource management in developing sustainable entrepreneurship and describes how human resource management practices and procedures are accustomed help entrepreneurs navigate their companies. Furthermore, this study was applied to 85 entrepreneurs who attended the “Entrepreneur Support Programme” within the Aegean Region of Turkey, supported by the Republic of Turkey Small and Medium Enterprises Development Organization (KOSGEB) in 2011. The obtained data from the questionnaires are analyzed through SPSS for Windows 17.0. It has resulted from the study that entrepreneurs have positive approaches toward human resource management contrary to our biases during the pre-survey period about entrepreneurs’ perceptions. Before conducting the survey, it had been expected from entrepreneurs that cash is the first important motivator for their start-up firms. However, results of the survey indicate that human is more important instead of money for entrepreneurs. On the opposite hand, surprisingly, entrepreneurs have a minimum of the average level of data on human resource management and its functions